Molecular Chaperones and Neurodegeneration - Cintia Roodveldt (Frontiers Research Topics, 2017)
Molecular chaperones or heat-shock proteins (HSPs) play essential roles in safeguarding structural stability and preventing misfolding and aggregation of proteins, and maintaining the proteome functionality in the cell. For over two decades until the present time, new functions have been discovered and several molecular mechanisms have been elucidated for many chaperones, while the field is being continuously challenged by new open questions. Probably as a consequence of the increasing research on the molecular bases of neurodegenerative diseases, and the realisation that many such disorders are linked to protein misfolding processes, unleashing the roles and mechanisms of chaperones in the context of neurodegeneration has become a prime scientific goal. This e-book contains a diversity of reviews, perspective and original research articles highlighting the importance and potential of this emerging subject.